Travestis, transsexuels et homosexuels dans le cinéma espagnol de la Transition démocratique (1975-1982): une interrogation à la nation - Emmanuel Le Vagueresse (Mélanges de la Casa de Velázquez, 2012)
This article looks at the proliferation of films dealing with homosexuality and other alternative sexualities (and their problems of gender) during Spain’s «Democratic Transition»—a special context which provided the freedom of form and content in which film-makers were able to portray «queens», in a blend of ghoulishness and empathy, as well as «new homosexuals» like the characters in the political films of Eloy de la Iglesia. Almodóvar’s cinema is a case apart, but many other feature-length films looked at what was coming to be known as the gay scene from a variety of angles, commercial or militant. But what all these films had in common was that they put a serious question to the Spanish nation that was in the process of construction and modernisation, which entailed the deconstruction of the myth of the «macho ibérico», without however demolishing the effeminate stereotype that the Spanish public found so reassuring.